Avaliação de características cinéticas e metabólicas de dois hibridomas para produção de anticorpos monoclonais para tipagem sanguínea - Silva, Bruna Gabriela (Universidade Federal de São Carlos, 2012)
The large scale production of monoclonal antibodies is the Biotechnology field that has achieved the biggest advances and realizations over the last 20 years, especially in the area of diagnosis and therapeutic applications. The world market of products for clinical diagnosis reached the value of US$ 19.0 billions in 2008 and continues to grow at a rate of 5 % per year. The development of bioprocesses of high productivity in large scale production of monoclonal antibodies (MAbs) depends on the determination and optimization of various kinetic and metabolic parameters of hybridomas. The aim of this study was to analyze kinetic and metabolic characteristics of murine hybridomas for production of immunoglobulins for blood typing by the ABO system, of great interest to the Brazilian public health. Three strains of murine hybridomas named ED7, ED9 and TAN generated in a brazilian research center to produce the antibodies anti-A, anti-B and anti-A,B, respectively, were evaluated for this purpose. Using only two lineage, ED7 and ED9, because of presenting bigger potential and stability for production of AMs in large scale, experiments of cultivation were carried out in spinner flask of 500 mL and in biorreator (Bioflo-110) of 2L, using culture media RPMI 1640 and MAb Quantum Yield-BD, both with addition of 10 % v/v of fetal bovine serum. The first one being the medium of origin of the hybrid clones, in some cases supplemented with amino acids (Gln, Met, Cys, Ser, Lys and Pro), and the second, a new alternative medium to which the hybridomas had to be adapted before the cultivation experiments. The results showed the need for additional nutritional balance of the media, especially RPMIS, to meet the nutritional demands of the two hybridomas. Through nutritional balance and cultivation in better controlled conditions in the bioreactor, it was possible to raise the maximum specific growth rate μmax from 0.0304 ± 0.0014 h-1 to ±0.0329 0.002 h-1 and the productivity of AM from 0.031 mg/L.h to 0.077 mg/L.h with the lineage ED7. With the lineage ED9 the μmax decreased from 0.0412 ± 0.0024 h-1 to 0.0373± h-1 but increased the productivity of AM from 0.030 mg / L.h to 0.040 mg / L.h. On the other hand, agglutination tests showed that the antibodies were functional and with titles stable and within normal limits. Despite the gains in productivity of the two AMs, the results highlighted a typical problem found in vitro cultivation of hybridomas, which is characterized by deregulation of its metabolism in the presence of high concentrations of glucose and glutamine, conduzing to overproction of the metabolites lactate and amonia. Because of this, one can predict that the future development of the bioprocess for the production of anti-A and anti-AB has to go through a stage of evaluation and system optimization in fed batch cultivation.
Keywords: Biotecnologia; Anticorpos monoclonais; Hibridoma; Tipagem sanguínea; ENGENHARIAS::ENGENHARIA QUIMICA